The Impact of Corruption on Commercial Banks’ Credit Risk - Alshareef, Ezuldeen Alhadi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
This research explores the influence of country wide corruption on the commercial banks’ credit risk. It applies the quantile regression (QR) estimation method for a panel data of 191 commercial banks from 18 MENAP nations, between the years 2011-2018. The research finding indicates that corruption significantly exacerbates the problem of bad loans of commercial banks. Furthermore, the QR results reveal that corruption does not affect all commercial banks at the same level. Commercial banks in higher quantiles (i.e. higher credit risk banks) appear to be affected more than the ones in lower quantiles (i.e. lower credit risk banks). Commercial banks with a high credit risk tend to be more vulnerable to corruption than commercial banks with low credit risk.

ÖZ: Bu araştırma, ülke çapındaki yolsuzluğun ticari bankaların kredi riski üzerindeki etkisini araştırmaktadır. 2011-2018 yılları arasında 18 MENAP ülkesinden 191 ticari bankanın panel verilerini kullanarak kantil regresyon tahmin yöntemini uygulamıştır. Araştırma bulguları, yolsuzluğun ticari bankaların sorunlu kredilerini önemli ölçüde artırdığını göstermektedir. Ayrıca, kantil regresyon sonuçları yolsuzluğun tüm ticari bankaları aynı düzeyde etkilemediğini ortaya koymaktadır. Daha yüksek kantillerdeki ticari bankalar, yani daha yüksek kredi riski taşıyan bankalar, düşük kantillerdekilerden, yani daha düşük kredi riskli bankalardan daha fazla etkilenmiş görünmektedir. Yüksek kredi riskine sahip ticari bankalar, düşük kredi riskine sahip ticari bankalara göre yolsuzluğa karşı daha savunmasız olma eğilimindedir.
Doctor of Philosophy in Finance. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2021. Supervisor: Prof. Dr. Hatice Jenkins
Keywords: Credit Risks--Banks and Banking; Corruption; MENAP countries; credit risk; quantile regression; commercial banks